Environmental and institutional factors influence on internet use by the undergraduate in selected federal universities in South-West, Nigeria (2012)
This study investigated the influence of environmental and Institutional factors on Internet use by undergraduate students in selected universities in South West, Nigeria. The study used undergraduate students in Obafemi Awolowo University (OAU) and Federal University of Agriculture, Abeokuta (FUNAlAB), Nigeria. The copies of the questionnaire designed for the study was administered on 1 78 purposively selected students from the selected universities out of which only 110 were returned with useful responses making a response rate of 61.8%. The study revealed reliable internet connection (Mean = 3.06), adequate infrastructural facilities (Mean = 2.62), Internet policy (Mean = 2.60), and ICT development policy (Mean = 2.54) as major environmental factors that influenced the use of internet among the students in the selected institutions. Also, the study established inadequate access points for internet use (Mean = 2.60), availability of adequate computer accessories (Mean - 2.55), high cost of internet use (Mean = 2.54), and adequate availability of computers connected to the Internet as major institutional factors that influenced the use of internet among the undergraduate students in the selected institutions. The study revealed that environmental factors significantly contribute positively to Internet use while institutional factors do not significantly influence internet use among undergraduate students in Nigerian universities.